Deliberation, political knowledge and vote choice: Results from an experiment with second-order elections. (September 2014) - Bernhagen, Patrick; Schmitt, Hermann
This article assesses the effects of deliberation and increased political knowledge on vote choice. The observed knowledge gains result from participation in a deliberative experiment in the context of second-order elections, which facilitates realistic estimates of information gains that can be expected if citizens were politically more engaged than they actually are. Using survey data on 333 participants in the deliberative experiment and 729 respondents from a control group, we find that deliberation is associated with significant changes in vote choice. Specifically, participating in the deliberative event is related to an increased likelihood of vote switching in favour of Green parties. However, there is no support for the expectation that changes in citizens' party choices are related to the observed increase in political knowledge.